PELATIHAN MENDELEY DAN TEKNIK ANALISIS DATA DENGAN EVIEWS - Husain Nurisman; Dian Surya Sampurna; Tutty Nuryati; Joko Bagio Santoso; Toto Aminoto; Bagus Styoko Purwo (Indonesian Community Service and Empowerment Journal (IComSE), 2022)
Pengabdian Kepada Masyarakat (PKM) is one of the three dharmas of university education, or the major responsibility of lecturers. This PKM activity is open to students completing their last year at private universities. PKM activities include the evaluation of "Mendeley Training and Data Analysis Techniques." PKM activities will take place online via the media zoom on July 31, 2021, from 8:00 a.m. to 12:00 a.m. WIB. The implementation team for this activity is led by a lecturer from STIE Indonesia in Rawamangun, East Jakarta, and comprises lecturers from the State University of Jakarta (UNJ). This activity is intended for students completing their last year at private universities who match the following criteria: There were 111 participants representing 24 universities from DKI Jakarta, West Java, Surabaya, Semarang, Yogyakarta, Padang, Bangka Belitung, Jember, and Samarinda. This community service activity (PKM) produces the following outputs: (1) Improving students' understanding of the thesis preparation process; (2) Improving students' understanding of the structure and proper citation of reference sources; and (3) Improving students' capacity to interpret research findings. Key words: pengabdian kepada masyarakat, microsoft word, mendeley, eviews